2001
DOI: 10.1183/09031936.01.99086801
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion reflects lung deposition of aminoglycoside aerosols in cystic fibrosis

Abstract: Using nebulization to deliver aminoglycosides may be of benefit in cystic fibrosis (CF) patients colonized byPseudomonas aeruginosa. However, one problem with this route is the absence of clinical parameters allowing estimation of the mass of drug deposited in the lungs (MDL). The aim of this study was to assess whether aminoglycoside excretion in the urine reflects the MDL.Fourteen studies were performed in seven CF patients. Amikacin was mixed with albumin labelled with99mTc and nebulized with an ultrasonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…24 The fact that urinary excretion actually reflects the lung deposition was confirmed earlier for the aminoglycoside, amikacin which, like SCG, is absorbed from the lungs but not orally. Typically, following inhalation of a radiolabeled aerosol, Dequin et al 25 found that a close correlation existed between the mass of drug deposited in the lungs (MDL) as determined by means of scintigraphy and the cumulative amount of amikacin excreted in urine.…”
Section: Discussionmentioning
confidence: 98%
“…24 The fact that urinary excretion actually reflects the lung deposition was confirmed earlier for the aminoglycoside, amikacin which, like SCG, is absorbed from the lungs but not orally. Typically, following inhalation of a radiolabeled aerosol, Dequin et al 25 found that a close correlation existed between the mass of drug deposited in the lungs (MDL) as determined by means of scintigraphy and the cumulative amount of amikacin excreted in urine.…”
Section: Discussionmentioning
confidence: 98%
“…Given the known safety profile of atropine (Volans, 1996), a critical patient may be nebulized twice in the first hour to produce sufficient atropinization, enough for him to be carried to the hospital for conventional treatment, which is the intravenous bolus route. Since systemic pharmacokinetics of any inhaled drug reflects its deposition in distal pulmonary regions (Dequin et al, 2001;Kumar et al, 2011), systemic absorption of nebulized AS proves that its absorption is also occurring mainly at the alveolar level, giving an additional proof of antidote's deep penetration into the lung parenchyma, and emphasizing its role in neutralizing inhaled toxicant in the lungs itself.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an intrathoracic deposition of~85% of the emitted aerosol (particle mass) was measured of which~77% was deposited in the peripheral lung [146]. A lung dose can be estimated by measuring the cumulative excretion of the drug during 24 h in the urine [147][148][149][150] or by radiodeposition studies [139,141,142,[151][152][153][154][155][156][157][158][159]. For newly developed inhalers, theoretical equivalent doses to current, standard inhalation treatment have been calculated, based on in vitro testing [160,161] or using a dose escalating method [162].…”
Section: Lung Dosementioning
confidence: 99%